Acoustically activated release of estrone-targeted liposomes used for breast cancer treatment - Mohammad, Najla (2016)
A Master of Science thesis in Chemical Engineering by Najla Mohammad entitled, "Acoustically activated release of estrone-targeted liposomes used for breast cancer treatment," submitted in January 2016. Thesis advisor is Dr. Ghaleb Al Husseini. Soft and hard copy available.